Sosialisasi Pengolahan Sampah Plastik Menjadi Paving Block Desa Tengah-Tengah, Kabupaten Maluku Tengah - Zulfikar Lating; Ira Deseilla Pawa (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
Health problems and environmental pollution can arise due to increased waste. Tengah-tengah Village is a village located on the coast where the problem is that most households do not have a rubbish dump and still throw rubbish around the house. The increasing amount of waste from day to day can cause a buildup of waste and result in environmental pollution. To reduce the amount of waste in Central Village, waste recycling is needed, especially plastic waste. One way to recycle plastic waste to make it attractive is to make paving blocks. The method used in this service is field visits in the form of providing outreach to the community and training in making paving blocks from plastic waste. The results of waste processing and how to make paving blocks from plastic waste received very good enthusiasm.